Leucine-Rich Repeat kinase 2 (LRRK2) - Rideout, Hardy J. (Springer, 2017)
This is the first book to assemble the leading researchers in the field of LRRK2 biology and neurology and provide a snapshot of the current state of knowledge, encompassing all major aspects of its function and dysfunction. The contributors are experts in cell biology and physiology, neurobiology, and medicinal chemistry, bringing a multidisciplinary perspective on the gene and its role in disease. The book covers the identification of LRRK2 as a major contributor to the pathogenesis of Parkinson's Disease. It also discusses the current state of the field after a decade of research, putative normal physiological roles of LRRK2, and the various pathways that have been identified in the search for the mechanism(s) of its induction of neurodegeneration.
Keywords: Neurogenetics.; Chromosomes.; Parkinson's disease -- Genetic aspects.; elektronické knihy; electronic books